2012
DOI: 10.1186/1745-6215-13-15
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Vitamin D Supplementation in Multiple Sclerosis (EVIDIMS Trial): study protocol for a randomized controlled trial

Abstract: BackgroundMultiple sclerosis is the most common chronic inflammatory disease of the central nervous system in young adults. Despite the fact that numerous lines of evidence link both the risk of disease development and the disease course to the serum level of 25-hydroxyvitamin D it still remains elusive whether multiple sclerosis patients benefit from boosting the serum level of 25-hydroxyvitamin D, mainly because interventional clinical trials that directly address the therapeutic effects of vitamin D in mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…Randomized controlled trials are currently underway to examine the effects of vitamin D supplementation on clinical and radiologic outcomes, with dosages of 5,000 to 10,000 IU daily. [23][24][25] …”
Section: High-dose Vitamin D Treatment Results In a Decrease In The Cmentioning
confidence: 99%
“…Randomized controlled trials are currently underway to examine the effects of vitamin D supplementation on clinical and radiologic outcomes, with dosages of 5,000 to 10,000 IU daily. [23][24][25] …”
Section: High-dose Vitamin D Treatment Results In a Decrease In The Cmentioning
confidence: 99%
“…A reduction of 1.5 new lesions in high-dose treatment is expected. The authors point out that the vitamin is safe, the treatment is cheap and that this study can fill the gaps that still exist regarding the immunomodulatory effects on Multiple Sclerosis [11].…”
Section: Discussionmentioning
confidence: 97%
“…Studies and sample protocols of that review showed that the reduction of injuries is expected in the intervention group with high dose of vitamin D3 [11], calcium levels remained normal, and there were no adverse effects [12][13][14][15][16][17][18][19]. It demonstrated that treatment with high dose of vitamin D3 lowers the proportion of IFN-ɣ and TCD4 +IL-17 and is safe.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] These trials, while mostly of sufficient dosages and duration to assess treatment efficacy, are quite small in sample size. Thus, we are anxiously awaiting the results of the larger trials, including SOLAR, 29 EVIDIMS 30 and PREVANZ. 31 The story of vitamin D/UVR and MS provides a nice example of how research evolves from the observations of patterns in data, leading to hypotheses as to mechanisms, and ultimately, leading to a consensus that factors are truly causally related to a disease or disease progression.…”
Section: The Contribution Of Epidemiological Research To Msmentioning
confidence: 99%